High efficiency and workflow of His bundle pacing and atrioventricular node ablation guided by three‐dimensional mapping system. Issue 10 (22nd September 2020) - Sun, Yuanjun; Yu, Xiaohong; Xiao, Xianjie; Yin, Xiaomeng; Gao, Lianjun; Zhang, Rongfeng; Dai, Shiyu; Wang, Nan; Zhang, Duoduo; Dong, Yingxue; Yang, Yanzong; Xia, Yunlong
Abstract: Background: Atrioventricular node (AVN) ablation combined with His bundle pacing is an effective strategy for permanent atrial fibrillation (AF) with rapid ventricular rate refractory to pharmacological therapy. We aimed to access the feasibility and efficiency of His bundle pacing and AVN ablation guided by three‐dimensional (3‐D) mapping system throughout the procedure. Methods: Eighteen patients with permanent AF with refractory rate and symptoms were referred for His bundle pacing and AVN ablation guided by 3‐D mapping (CARTO3). Electroanatomic 3‐D mapping of the right atrium and right ventricle was performed by the ablation catheter with CARTO 3 system, followed by the visualization of the leads for implantation and AVN ablation. Results: Implantation of His bundle and ventricular leads and AVN ablation were achieved successfully with the help of 3‐D mapping in 17 patients. Selective His bundle pacing was achieved in five patients (29.4%), and the other (70.6%) were nonselective His bundle pacing. The mean procedure duration was 99.4 ± 16.4 minutes. The mean fluoroscopy time was 7.0 ± 2.6 minutes. The time spent on His lead implantation was 6.1 ± 3.2 minutes. One patient experienced AVN ablation from left side under aortic valves due to no effect of ablation in right atrium. Conclusion: His bundle pacing and AVN ablation guided by throughout real‐time 3‐D mapping system are of high‐efficiency and feasibility.